2020
DOI: 10.21203/rs.3.rs-107106/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alterations in the Histological Features of the Intestinal Mucosa in Malnourished Adults of Bangladesh

Abstract: There is paucity of knowledge on the histological features of the intestinal mucosa in malnourished adults of Bangladesh. The purpose of the study was to explore the histological features of the intestinal mucosa in malnourished adults of Bangladesh and to compare the findings with their well-nourished counterparts. 64 adults (37 malnourished with body mass index, BMI<18.5 kg/m2 and 27 controls with BMI>18.5 kg/m2) from the Bangladesh Environmental Enteric Dysfunction (BEED) study, who underwent upper-ga… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Numerous studies were conducted to investigate pathologies of the stomach and esophagus 25 , but only a few explored duodenal pathologies, especially in children 25 . A similar study on malnourished adults has revealed very high prevalence of non-specific duodenitis based on histopathological evidence 18 . A study aimed to explore H. pylori associated dyspepsia in children residing in urban slums has also shown a high prevalence of asymptomatic duodenitis 26 .…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Numerous studies were conducted to investigate pathologies of the stomach and esophagus 25 , but only a few explored duodenal pathologies, especially in children 25 . A similar study on malnourished adults has revealed very high prevalence of non-specific duodenitis based on histopathological evidence 18 . A study aimed to explore H. pylori associated dyspepsia in children residing in urban slums has also shown a high prevalence of asymptomatic duodenitis 26 .…”
Section: Discussionmentioning
confidence: 82%
“…A higher number of infiltrates than normal was defined as mild cellular infiltration. Figure 2 shows the schematic representation used for the assessment of the morphological changes described above 18 . Figure 2.…”
Section: Definition Of Duodenitis and Evaluation Of Intestinal Histo-...mentioning
confidence: 99%
See 2 more Smart Citations
“…The villous height, crypt depth, intraepithelial lymphocytes (IELs) and presence of inflammatory infiltrates in the lamina propria were determined from the biopsied specimens. Abnormalities in intestinal histological characteristics (villous atrophy, crypt hyperplasia, inflammatory infiltrates in lamina propria and IELs) were defined according to the literature published elsewhere 17 .…”
Section: Methodsmentioning
confidence: 99%